Development of Mathematics Learning Tools with Problem Based Learning Model on Matrix Material to Facilitate Students' Critical Thinking Ability - Pertiwi, Wiyana; Roza, Yenita; Yuanita, Putri (FKIP-Universitas Riau, 2021)
The ability of students to think critically in mathematics is is still low. The lack of learning tools that are considered to facilitate students' mathematical critical thinking skills is one of the cause it. The purpose of this study was to develop a mathematics learning tool with a quality problem-based learning (PBM) model to facilitate students' mathematical critical thinking skills. The learning tools developed consisted of a syllabus, lesson plans (RPP) and student worksheets (LKPD) on the matrix material for class X SMK. This research was a development research using the Borg and Gall model. The development consists of six stages, namely: 1) research and data collection; 2) planning; 3) development of the initial product draft; 4) initial field trials; 5) revised trial results; and 6) dissemination and implementation. The subject of this research trial was the students of SMK Nurul Falah Pekanbaru. The instrument used was validation instrument for the syllabus, lesson plans, and student worksheet. Based on the results of the validation data analysis, it shows that the learning tools developed were very valid. The results of the validation of the syllabus were 85.11; the average RPP score was 86.02; and the average LKPD score was 86.40. The average student response questionnaire to the initial field trial was 85.93 with the very practical category. The learning device developed was valid and practical for use by class X SMK students.